2018
DOI: 10.1111/jth.13909
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical prediction model for the postthrombotic syndrome in a prospective cohort of patients with proximal deep vein thrombosis

Abstract: Background Postthrombotic syndrome (PTS) is a chronic complication that develops in 20-50% of patients after deep vein thrombosis (DVT). Although individual risk factors for PTS have been characterized, the ability to predict which DVT patients are likely to develop PTS remains limited. Objective To develop a clinical prediction score for PTS in patients with DVT. Methods The derivation cohort consisted of participants in the SOX Trial, a randomized double-blind placebo-controlled trial of elastic compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 32 publications
(60 reference statements)
1
58
0
3
Order By: Relevance
“…Previous studies have also found iliofemoral DVT (2,44), recurrent ipsilateral DVT (2,39,46,49), and high body mass index (BMI) (35) as strong predictors for PTS (44,48). DVT with pelvic vein involvement were included in our multivariate model but was not a signi cant predictor in our study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous studies have also found iliofemoral DVT (2,44), recurrent ipsilateral DVT (2,39,46,49), and high body mass index (BMI) (35) as strong predictors for PTS (44,48). DVT with pelvic vein involvement were included in our multivariate model but was not a signi cant predictor in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Others have also found that a higher baseline Villalta score predicts a less favorable long-term outcome. Rabinovich et al developed a prediction model for PTS based on the SOX study and found that patients with a Villalta score ≥ 4 at baseline, in addition to pelvic DVT and body mass index ≥ 35kg/m 2 , predicted increased risk of PTS (48).…”
Section: Discussionmentioning
confidence: 99%
“…In the post hoc analysis of the SOX trial cohort, the SOX -PTS index was calculated and proposed (19). The high predictors of the PTS occurrence were the following factors from the baseline assessment: iliac vein DVT (1 point), BMI > 35 (2), Villalta score 9-14 at baseline (1), Villalta score > `14 at baseline (1).…”
Section: Post-thrombotic Syndrome Predictive Modelsmentioning
confidence: 99%
“…The rationale for the derivation of a secondary model was, that for some forms of treatment it is conceivable that they are most effective in the acute and sub‐acute phase and might therefore be stopped in selected patients at low risk after this initial period. Rabinovich et al . presented a model, which based the outcome PTS on the Ginsberg score .…”
Section: Barriers To Progress and Future Perspectivesmentioning
confidence: 99%